2020
DOI: 10.1055/a-1113-7343
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Volume Measurement in Cervical and Intracranial Arteries using Quantitative Magnetic Resonance Angiography and Duplex Sonography (Bocaccia) – A Prospective Observational Study

Abstract: Purpose Cerebral blood flow volume is an important factor for the accurate diagnosis of neurovascular diseases and treatment indication. This study aims to assess correlations of blood flow volume measurements in cervical and intracranial arteries between duplex sonography and quantitative magnetic resonance angiography (qMRA). Materials and Methods Consecutive patients with suspicion of cerebral vascular pathology underwent qMRA and duplex sonography of cervical and intracranial arteries with measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Thus, the correlation coefficient between the values of the BFV in the internal carotid artery (ICA) using these methods was about 0.75 (P < .01), and in the vertebral arteries (VAs) 0.78 (P < .01). 2 Studies of the BFV in brain-supplying arteries using duplex sonography (DS) are still few in number. In addition to those in healthy individuals, 3,4 a number of authors reported on the results of evaluation of BFV in VA hypoplasia, 5 dementia, 6 panic attacks, 7 and fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the correlation coefficient between the values of the BFV in the internal carotid artery (ICA) using these methods was about 0.75 (P < .01), and in the vertebral arteries (VAs) 0.78 (P < .01). 2 Studies of the BFV in brain-supplying arteries using duplex sonography (DS) are still few in number. In addition to those in healthy individuals, 3,4 a number of authors reported on the results of evaluation of BFV in VA hypoplasia, 5 dementia, 6 panic attacks, 7 and fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%